The Influence of Transformational Leadership Style on The Work Motivation of Parepare City Health Service Employees With The Work Environment As a Mediation Variable - Tasrif Tasrif; Nur Asisah (Economos : Jurnal Ekonomi dan Bisnis, 2022)
The Influence of Transformational Leadership Style On Employee Work Motivation With Work Environment As A Mediation Variable". This study aims to know 1) The influence of transformational leadership style on work motivation, 2) The influence of leadership style on the work environment 3) The influence of the work environment on work motivation, 4) The influence of leadership style on work motivation with the work environment as a mediator. The data collection techniques used are observation and distribution of questionnaires. The population in this study was all employees of the ASN (State Civil Apparatus) of the Parepare City Health Service which amounted to 348 with a proportionate stratified sampling technique randem sampling 50% peer sample so that a peer sample of 177 respondents was obtained.the data acquisition technique used was the SEM-PLS (Structural Equation Modeling-Partial Least Square) analysis technique. by using the WarpPLS 7.0 application. The results of this study are 1) Transformational leadership style has a significant effect on employee work motivation, 2) Leadership style has a significant effect on the work environment, 3) The work environment has a significant effect on employee work motivation, and 4) Leadership style has a significant effect on employee work motivation and is mediated by the work environment